2018
DOI: 10.1590/rbz4720170153
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of apparent metabolizable energy and metabolizable energy corrected for nitrogen of corn according to physical classification of the grain

Abstract: The objective of this study was to develop an equation to determine the apparent metabolizable energy (AME) and metabolizable energy corrected for nitrogen balance (AMEn) using a physical-based classification of corn. A total of 5,055 samples were taken from bulk cargo trucks, over a five-year period. The parameters studied were the variables related to the physical characteristics of grains. The density of maize was evaluated, and AME and AMEn were calculated. The average value for AME was 3,375 kcal/kg, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
0
3
3
Order By: Relevance
“…Regarding AMEn FM , the same behavior displayed 2), occurred due to the decreasing DM content of the kernels as their specific gravity increased. The AMEn FM values found in the present study were lower than those cited in the literature (4,8,14) (3247 to 3562 kcal/kg), but higher than the 2937 kcal/kg found by Silva et al (14) in maize fractions of low specific gravity.…”
Section: Resultscontrasting
confidence: 83%
See 4 more Smart Citations
“…Regarding AMEn FM , the same behavior displayed 2), occurred due to the decreasing DM content of the kernels as their specific gravity increased. The AMEn FM values found in the present study were lower than those cited in the literature (4,8,14) (3247 to 3562 kcal/kg), but higher than the 2937 kcal/kg found by Silva et al (14) in maize fractions of low specific gravity.…”
Section: Resultscontrasting
confidence: 83%
“…The MC CP values found did not differ statistically between the maize specific gravity fractions (P>0.05) (Table 5). The MC CP values and CP levels (Table 3) were lower than those recommended in the Brazilian food composition table 7 (87% MC CP ), but higher than the mean value of 57.3% found by Rodrigues et al (8) in different maize fractions. These results suggest that, in the present study, the higher CP level found at the lowest specific gravity fraction, resulting from the lower starch concentration in these kernels, did not influence the levels of digestible amino acids or low-nutritional-value zein proteins (10) .…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations